Mechanochemical Processing of Cacu3ti4o12 with Giant Dielectric Properties - (:unkn) unknown (TAYLOR & FRANCIS INC, 2014)
The dielectric properties of CaCu3Ti4O12 (CCTO) ceramic prepared by mechanochemical synthesis (MCS) were investigated. The effect on dielectric properties of ball-to-powder weight ratio and milling time was investigated and compared to the behavior of CCTO prepared by conventional solid state reaction (CSSR). CCTO ceramic was partially obtained after 6h of the milling process, while complete transformation was obtained during the sintering step of milled powders. It was shown that the dielectric properties of CCTO processed by MCS are dramatically improved compared with samples prepared by CSSR.